Problems with L2 classroom research in the SEN setting with visually challenged learners - Jedynak, Małgorzata (Glottodidactica, 2012)
The paper highlights the what, the why and the how questions which may be posed by the novice researcher in the field of visual impairment. I discuss the problematic issues inherent to various stages of research preparation and implementation such as selection of a research method, recruitment of subjects for a study, the lack of theories and models in the field of visual impairment, applicability and administration of standard tests in the SEN setting, keeping up participants’ commitment throughout a project, or sustainment of the researcher’s emotional involvement.